THE EXPRESSION OF NATIONAL MENTALITY AND LOCAL COLOR IN THE WORKS OF ABDULLAH SHER (Scientific journal of the Fergana State University, 2023)
In this article the national spirit and local color of the creation of Abdulla Sher is analyzed.